What differences? Thematic analyses of blended learning researches in Iran. (2nd October 2022) - Seraji, Farhad
ABSTRACT: In the present era, blended learning (BL) is one of the most frequently used concepts related to integrating Information and Communications Technology (ICT) with the curriculum. Numerous research is conducted annually in the field of blended learning in different regions of the world. The purpose of the present research is to determine the status of blended learning researches in Iran. For this, 60 articles were selected, using systematic review and observing inclusion and exclusion criteria, and analysed based on six themes including terminology, methodology, topic, blending level, context and technology. The results revealed that the researches on blended learning in Iran are similar to international studies in some themes such as terminology, context and blending level and different in other themes including topic, methodology and terminology. Based on the findings, suggestions are made for international and Iranian blended learning researchers.